Advances in Legume Research - Susana S. Araújo (Frontiers Research Topics, 2018)
Legumes crops have an extraordinary importance for the agriculture and the environment. In a world urgently requiring more sustainable agriculture, food security and healthier diets the demand for legume crops is on the rise. The International Legume Society (http://ils.nsseme.com) organizes a triannual series of conferences with the goal to serve as a forum to discuss interdisciplinary progress on legume research. The Second International Legume Society Conference (ILS2) hosted in October 2016 at Troia, Portugal was the starting point for the Research Topic "Advances in Legume Research" in FiPS, that was also open to spontaneous submissions.